Research of the effectiveness of equity capital by chemical industry companies during the crisis - O. V. Berezhnaya; E. V. Berezhnaya (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In crisis and post-crisis periods, financial support for company activities becomes important. Equity is becoming the main source, and requirements for the efficiency of its use are growing. At the same time, the efficiency of using equity capital largely depends on the specifics of the core activities and the effectiveness of a company. The structure of funding sources, which are subject to fluctuations during periods of crisis, plays a significant role.Goal. The purpose of the work is to assess the effectiveness of using their own sources of financing, typical for companies in the chemical industry, during the period of crisis and sanctions restrictions from 2019 to 2022.Materials and methods. Based on traditional methods of statistical analysis, financial analysis and classical deterministic models (in particular, return on equity capital), on the basis of information on the financial results and capital structure of organizations in the SPARK-Interfax system, the authors analyzed the dynamics of equity capital, its components in the chemical industry and its sub-sectors. The study makes an assessment of the efficiency of using equity capital and the factors that determine it. The analysis was carried out on the basis of industry average indicators and is important for tracking industry development trends and making macro- and mesoeconomic decisions.Results and discussion. The indicators of the authorized capital and its changes in 2019 – 2022 were studied, the trends in changes in the financial stability of companies under conditions of crisis and sanctions pressure were assessed. The factors influencing the return on equity in the context of types of activities in chemical production were analyzed. The features of the activities of chemical companies that influenced their financial results during the study period are highlighted.Conclusion. Conclusions are drawn about the resistance of chemical industry companies to the influence of destabilizing factors and further directions for research into the structure and efficiency of using sources of financing for companies in a particular industry.